Box Jacking/Pushing Method for Tunnel Construction in Rock: Doha Metro, Gold Line Project - Konstantis, Spyridon; Massinas, Spyros (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The case of a box pushing tunneling method in rock, on Doha Metro Gold Line project, successfully implemented to connect multiple entrance structures of Sport City station under a live traffic junction, in a heavy urban environment and under very shallow overburden is presented. Due to the size of the underpasses, the need to maintain uninterrupted traffic and the time-consuming utility diversions and reinstatement, the use of conventional NATM and Cut and Cover methods were assessed as either non-feasible or of high risk. The dimensions of the unsupported span, the encountered geotechnical conditions, the development of the settlements at road level and the box advance rate are presented